2004
DOI: 10.1590/s0103-84782004000400046
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade entre plantas de azevém para caracteres relacionados à precocidade

Abstract: RESUMO O objetivo deste trabalho foi estudar a variabilidade intrapopulacional existente para caracteres relacionados à produção precoce de matéria seca e duração do ciclo vegetativo em uma população de azevém anual (Lolium multiflorum). Foram avaliadas 500 plantas para o número deOs caracteres realmente importantes em uma espécie forrageira são aqueles que afetam o desenvolvimento das plantas, a persistência e o valor nutritivo, mas a importância relativa de cada caráter dependerá em grande parte dos estresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The NH and diameter traits measured in the initial stage of the plant development with the objective of selecting for early dry matter production has shown a certain degree of association (r = 0.35), besides having a negative correlation with heading date, which might point to a tendency of delayed flowering progenies for having a slower initial development. Mittelmann et al (2004) have found similar correlations, and considered that they are of low value and do not hind the selection for an extended cycle of utilization of the pasture.…”
Section: Resultsmentioning
confidence: 75%
“…The NH and diameter traits measured in the initial stage of the plant development with the objective of selecting for early dry matter production has shown a certain degree of association (r = 0.35), besides having a negative correlation with heading date, which might point to a tendency of delayed flowering progenies for having a slower initial development. Mittelmann et al (2004) have found similar correlations, and considered that they are of low value and do not hind the selection for an extended cycle of utilization of the pasture.…”
Section: Resultsmentioning
confidence: 75%
“…Ryegrass (Lolium multiflorum L.), belonging to the Poaceae family, is a high-productivity crop and has not yet been used in human food. This cereal is a potential candidate for innovation and to increase the worldwide supply of food due to its morphological, agronomic, and nutritional characteristics, highlighting the easy dispersion and adaptation to low and medium fertility soils and pest resistance, among others, and having easy adaptation in countries with partial or total territory located below the Capricorn or above the Cancer Tropics [4].…”
Section: Introductionmentioning
confidence: 99%